2023
DOI: 10.1007/s00253-023-12490-8
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of potent neutralizing antibodies in obese mice by ISA 51-adjuvanted SARS-CoV-2 spike RBD-Fc vaccine

Abstract: Vaccination is considered to be the most effective countermeasure to prevent and combat the global health threats of COVID-19. People with obesity are at a greater risk of hospitalization, life-threatening illness, and adverse outcomes after having COVID-19. Therefore, a safe and effective COVID-19 vaccine for obese individuals is urgently needed. In the study, the vaccine composed of the ISA 51 adjuvant and the SARS-CoV-2 spike (S) receptor-binding domain (RBD) in conjugation with the human IgG1 Fc fragment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
(78 reference statements)
2
2
0
Order By: Relevance
“…This implied that RBD-based vaccine could elicit sufficient neutralizing antibodies when compared to whole spike candidate. These results were also consistent with other reports of RBD-Fc-based vaccine development that RBD-Fc shows high potency as vaccine candidate against SARS-CoV-2 [17,[19][20][21][22][23][24].…”
Section: Plos Onesupporting
confidence: 93%
See 3 more Smart Citations
“…This implied that RBD-based vaccine could elicit sufficient neutralizing antibodies when compared to whole spike candidate. These results were also consistent with other reports of RBD-Fc-based vaccine development that RBD-Fc shows high potency as vaccine candidate against SARS-CoV-2 [17,[19][20][21][22][23][24].…”
Section: Plos Onesupporting
confidence: 93%
“…Combining these results with the result of primary structure analysis using MS/MS, it was confirmed that CHO-produced RBD-Fc could display native-like properties. This results also were consistent with previous studies where RBD-Fc vaccine obtained from mammalian cell expression system exhibited desired biochemical characteristics [19][20][21]24].…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations